2003
DOI: 10.1074/jbc.m302091200
|View full text |Cite
|
Sign up to set email alerts
|

Small Conductance Ca2+-activated K+ Channels and Calmodulin

Abstract: Small conductance Ca2؉ -activated K ؉ channels (SK channels) are heteromeric complexes of pore-forming ␣ subunits and constitutively bound calmodulin (CaM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 46 publications
4
83
1
Order By: Relevance
“…1 and 4). CaM is not only essential for gating but is also required for channel assembly and trafficking (28). Our data demonstrate that targeting or anchoring of SK2 channel at the plasma membrane requires the binding of ␣-actinin2, which crosslinks actin filaments to stabilize the muscle contractile apparatus and signal transduction.…”
Section: ␣-Actinin2mentioning
confidence: 75%
“…1 and 4). CaM is not only essential for gating but is also required for channel assembly and trafficking (28). Our data demonstrate that targeting or anchoring of SK2 channel at the plasma membrane requires the binding of ␣-actinin2, which crosslinks actin filaments to stabilize the muscle contractile apparatus and signal transduction.…”
Section: ␣-Actinin2mentioning
confidence: 75%
“…We found that CaM provides a Ca 2ϩ -dependent acceleration of channel trafficking to distal regions of dendrites in hippocampal neurons. This adds to a growing list of examples in which CaM, as a constitutive subunit, modulates steps in channel biosynthesis such as trafficking of SK K ϩ channels (Joiner et al, 2001;Lee et al, 2003) or assembly of KCNQ1 K ϩ channels (Ghosh et al, 2006;Shamgar et al, 2006). For Ca 2ϩ / CaM acceleration of ␣ 1C trafficking, two results suggest that the mechanism of action for CaM most likely involves an interaction with the CaM binding pocket.…”
Section: Discussionmentioning
confidence: 93%
“…Although a great deal has been learned about the second messenger-dependent regulation of these KCa channels in terms of altering P o (15)(16)(17)(18)(19)(20)(21), much less information exists regarding the mechanisms by which N is determined. We (20,(22)(23)(24) and others (25)(26)(27) have identified numerous motifs in the N and C termini of KCa2.3 and KCa3.1, which are required for the proper assembly and anterograde trafficking of these channels to the plasma membrane. However, to date, no studies have defined the retrograde transport of KCa2.3 or KCa3.1 from the plasma membrane.…”
mentioning
confidence: 76%
“…To determine which portion of KCa2.3 dictates its long half-life, and presumably its recycling, we generated two chimeras in which either the entire cytoplasmic C terminus of KCa3.1 (Arg 287 -Lys 427 ) was appended onto S6 of KCa2.3 (Fig. 10A, KCa2.3-287KCa3.1) or the N terminus of KCa3.1 (Met 1 -Ala 26 ) was appended to S1 of KCa2.3 (Fig. 10B, 26KCa3.1-KCa2.3).…”
Section: Recycling Of Kca23 Is Dependent Upon Rab35 and The Rab35 Gamentioning
confidence: 99%